Effective reprogramming of patient-derived M2-polarized glioblastoma-associated mcroglia/macrophages by treatment with GW2580 - Fermi, Valentina; Warta, Rolf; Wöllner, Amélie; Lotsch, Catharina; Jassowicz, Lena; Rapp, Carmen; Knoll, Maximilian; Jungwirth, Gerhard; Jungk, Christine; Dao Trong, Huy Philip; Deimling, Andreas von; Abdollahi, Amir; et al. (Clinical cancer research, 2023)
Purpose: Targeting immunosuppressive and pro-tumorigenic glioblastoma (GBM)-associated macrophages and microglial cells (GAM) has great potential to improve patient outcomes. Colonystimulating factor-1 receptor (CSF1R) has emerged as a promising target for reprograming anti-inﬂammatory M2-like GAMs. However, treatment data on patient-derived, tumor-educated GAMs and their inﬂuence on the adaptive immunity are lacking.
Gesehen am 13.05.2024